In Search of the Encounter between Religion and Mathematics - Wiwit Kurniawan; Tri Hidayati (International Journal of Social Science and Religion (IJSSR), 2020)
Religion and mathematics are perceived as two things that are very reciprocally exclusive; this is due to the opinion asserting that mathematics is considered as valid and objective knowledge. On the other hand, religion is something interpretive and subjective. Historically speaking, religion and mathematics have a strong association and in certain aspects, both of them have points of contact that can permeate each other. The forms of intersection between mathematics and religion need to be analyzed so that we will be able to see more clearly the current religious phenomenon. This study investigates and discovers a potential encounter between religion and mathematics. To see the relationship between religion and mathematics, and even their fusion, the first thing to do is determine the definition of religion and mathematics. With a clear understanding of both, the encounter points will be easier to recognize. The research method used in this study is a literature review. This study collects systematically a variety of literature related to the theme under study. The encounter between religion and mathematics undergoes at five dimensions, they are ontological, epistemological, teleological, theoretical and application dimension. This study more focused on similarities to reveal the connection between religion and mathematics.